Faktor-Faktor Yang Mempengaruhi Niat UMKM di Kota Padang Menggunakan e-Payment sebagai Metode Pembayaran - Lidya Namira (Owner : Riset dan Jurnal Akuntansi, 2022)
Technological developments are experiencing rapid progress which will provide convenience in accessing information and in managing resources effectively and efficiently. This development has also spawned innovations, especially in financial technology that can facilitate public access to financial services, one of which is e-Payment. This study aims to obtain empirical evidence regarding the effect of perceived benefits, perceived ease of use and perceived risk on MSME's intention to use e-Payment as a Payment Method. This study uses a theory, namely The Theory Acceptance Model (TAM) which is modified by adding a risk perception variable. The data used in this study are primary data obtained from online questionnaires distributed to 95 MSMEs throughout the city of Padang which were selected using the non-probability sampling method with the Slovin formula. The data analysis technique used is SEM (Structural Equation Model) using SmartPLS 3.0 software. From the results of this study indicate that of all the constructs that have been tested, namely the perception of benefits, ease of use and risk affect the intention of MSMEs in using e-Payment as a payment method. In this study, the TAM theory coupled with risk perception has proven that the independent variable in this study can explain its influence on the behavioral intention variable by 48.5% on the intention variable.